Molecular basis for the inhibition of the methyl-lysine binding function of 53BP1 by TIRR - Jiaxu Wang (Nature Portfolio, 2018)
Tudor interacting repair regulator (TIRR) is a negative regulator of 53BP1 in DNA damage repair processes. Here the authors give mechanistic insights into how TIRR mediates suppression by solving the crystal structure of TIRR bound to the 53BP1 tandem Tudor domain (TTD).